2018
DOI: 10.3847/1538-4357/aaa963
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Near-IR, and Sub-mm IFU Observations of the Nearby Dual Active Galactic Nuclei MRK 463

Abstract: We present optical and near-IR Integral Field Unit (IFU) and ALMA band 6 observations of the nearby dual Active Galactic Nuclei (AGN) Mrk 463. At a distance of 210 Mpc, and a nuclear separation of ∼4 kpc, Mrk 463 is an excellent laboratory to study the gas dynamics, star formation processes and supermassive black hole (SMBH) accretion in a late-stage gas-rich major galaxy merger. The IFU observations reveal a complex morphology, including tidal tails, starforming clumps, and emission line regions. The optical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 108 publications
3
28
1
Order By: Relevance
“…Information about the gas geometry and kinematics from high spatial resolution ionized and molecular emission line mapping is required to associate the different absorbing components with the emitting regions. For example, multi-wavelength IFU observations of the merger Mrk 463 presented in Treister et al (2018) suggests that while there exists significant reservoir of molecular gas around the double nuclei, only a small fraction of it is feeding the SMBH. More such studies are required to understand the relationship between neutral gas in mergers and AGN activity.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the gas geometry and kinematics from high spatial resolution ionized and molecular emission line mapping is required to associate the different absorbing components with the emitting regions. For example, multi-wavelength IFU observations of the merger Mrk 463 presented in Treister et al (2018) suggests that while there exists significant reservoir of molecular gas around the double nuclei, only a small fraction of it is feeding the SMBH. More such studies are required to understand the relationship between neutral gas in mergers and AGN activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the CO molecule can be easily excited even in cold environments and is relatively abundant, making it an important tracer of the molecular gas contents of a galaxy. In order to convert from observed 12 CO(2-1) line flux to total molecular gas mass we follow the procedure described by Solomon & Vanden Bout (2005), as done previously by Treister et al (2018). Specifically, the line luminosity is computed from the observed line flux as…”
Section: Gas Mass From 12 Co(2-1)mentioning
confidence: 99%
“…The first concrete evidence for dual AGNs was a serendipitous discovery by Chandra in NGC 6240 (Komossa et al 2003), a z = 0.02 merging ultra-luminous infrared galaxy (ULIRG), which contains two X-ray nuclei separated by ∼ 1 (∼ 0.7 kpc) in projection. Until recently only a handful of other secure cases were known in the X-rays (e.g., 3C 75 (Hudson et al 2006), Mrk 463 (Bianchi et al 2008;Treister et al 2018), Mrk 266 (Brassington et al 2007Mazzarella et al 2012), and Mrk 739 (Koss et al 2011); but see also Arp 299 (Ballo et al 2004) for a candidate), all of which were confirmed by Chandra.…”
Section: Introductionmentioning
confidence: 99%